Legal Protection of Patients and the Responsibilities of Medical Personnel in the Implementation of Health Services in Indonesia: A Normative Juridical Approach - Lili Andriani Gofar (Journal of Law and Humanities Review, 2026)
Health services are part of the fulfillment of fundamental human rights which in its implementation involves legal relations between patients, medical personnel, health workers, health service facilities, professional organizations, and the government. The enactment of Law Number 17 of 2023 concerning Health brings important changes to the construction of Indonesian health law because it integrates various health regulations that were previously scattered in a number of sectoral laws. This research aims to analyze the legal protection of patients, the responsibilities of medical personnel, the position of informed consent, patient safety, and legal developments after the enactment of Law No. 17 of 2023. The research uses normative juridical methods with statutory approaches, conceptual approaches, case approaches, and analytical approaches. The primary legal material consists of the 1945 Constitution of the Republic of Indonesia, Law No. 17 of 2023, Government Regulation No. 28 of 2024, and relevant Constitutional Court decisions. Secondary legal materials are in the form of legal journals, health journals, health law books, and legal doctrine. The results of the study show that Law No. 17 of 2023 has provided a relatively comprehensive basis for protection for patients and medical personnel, including through the regulation of patient rights, medical personnel rights, professional obligations, approval of health service actions, confidentiality of health data, and professional discipline mechanisms. However, there are still issues regarding legal certainty, the boundary between medical risk and negligence, dispute resolution mechanisms, health data protection, and the division of authority between the government and professional institutions. Constitutional Court Decision No. 111/PUU-XXII/2024 strengthens the independent position of the Collegium as an element of the Council's membership and provides constitutional meaning to a number of norms of the Health Law. This research offers a legal protection model that places patient rights, medical personnel protection, patient safety, professionalism, and state responsibility in one balanced framework.